2013
DOI: 10.1165/rcmb.2013-0070oc
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic Acid Receptor–2 Deficiency Confers Protection against Bleomycin-Induced Lung Injury and Fibrosis in Mice

Abstract: Idiopathic pulmonary fibrosis is a devastating disease characterized by alveolar epithelial cell injury, the accumulation of fibroblasts/ myofibroblasts, and the deposition of extracellular matrix proteins. Lysophosphatidic acid (LPA) signaling through its G proteincoupled receptors is critical for its various biological functions. Recently, LPA and LPA receptor 1 were implicated in lung fibrogenesis. However, the role of other LPA receptors in fibrosis remains unclear. Here, we use a bleomycin-induced pulmona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
103
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(105 citation statements)
references
References 49 publications
2
103
0
Order By: Relevance
“…Bleomycininduced pulmonary fibrosis is the most widely studied mouse model of pulmonary fibrosis (Moore et al, 2013) and may also develop in humans treated with bleomycin for a variety of cancers. Mice genetically deficient for LPA 1 or LPA 2 are significantly protected from fibrosis and mortality in this model (Tager et al, 2008;Huang et al, 2013). We also found that LPA 1 was highly expressed by fibroblasts recovered from BAL fluid of persons with IPF, and inhibition of LPA 1 markedly reduced fibroblast responses to the chemotactic activity present in their BAL fluid (Tager et al, 2008), demonstrating the potential relevance of LPA 1 to human pulmonary fibrosis.…”
Section: A Lysophosphatidic Acidmentioning
confidence: 52%
See 1 more Smart Citation
“…Bleomycininduced pulmonary fibrosis is the most widely studied mouse model of pulmonary fibrosis (Moore et al, 2013) and may also develop in humans treated with bleomycin for a variety of cancers. Mice genetically deficient for LPA 1 or LPA 2 are significantly protected from fibrosis and mortality in this model (Tager et al, 2008;Huang et al, 2013). We also found that LPA 1 was highly expressed by fibroblasts recovered from BAL fluid of persons with IPF, and inhibition of LPA 1 markedly reduced fibroblast responses to the chemotactic activity present in their BAL fluid (Tager et al, 2008), demonstrating the potential relevance of LPA 1 to human pulmonary fibrosis.…”
Section: A Lysophosphatidic Acidmentioning
confidence: 52%
“…LPA signaling through two of its receptors, LPA 1 and LPA 2 , is shown be required for the development of pulmonary fibrosis in mouse models (Tager et al, 2008;Huang et al, 2013). We found that LPA levels are increased in the bronchoalveolar lavage (BAL) fluid acquired from persons with IPF compared with healthy controls.…”
Section: A Lysophosphatidic Acidmentioning
confidence: 86%
“…The subsequent cell growth can result in the pathogenic fi broblast proliferation seen in fi brosis. Lpar2 may also be involved in pulmonary fi brosis, as knockout mice demonstrated protection against bleomycin-induced lung injury, fi brosis, and death (248). In addition, LPA and ATX levels not by 16:0 LPA or 18:0 LPA (223).…”
Section: Fibrosismentioning
confidence: 99%
“…In light of the poor prognosis and lack of available antiinflammatory therapies, there is a pressing need for alternative approaches including evaluation of new targets and pathways in animal models of fibrosis. Accordingly, two bioactive lipids, lysophosphatidic acid and sphingosine-1-phosphate, and enzymes involved in their metabolism have been implicated in regulating the development of pulmonary fibrosis (7)(8)(9)(10)(11).…”
mentioning
confidence: 99%